Membangun Komitmen Guru: Peran Iklim Organisasi dan Kepuasan Kerja di Lingkungan Sekolah Menengah - Berlian Ica Herawati; Adnani Budi Utami; Sayidah Aulia Ul Haque (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Teacher commitment is a critical factor in the success of educational outcomes. However, a significant number of teachers continue to exhibit low levels of commitment, as reflected in limited involvement in student mentoring, inadequate preparation for teaching and learning activities, poor adherence to school regulations, and a tendency to seek alternative employment outside the teaching profession. This lack of commitment is believed to be influenced by various factors, including the organizational climate and job satisfaction. This study aims to investigate the relationship between organizational climate and job satisfaction with teacher commitment. A quantitative correlational approach was employed, using total sampling of 125 high school teachers in Menganti District, Gresik. Data were analyzed using Spearman’s Rho test with the assistance of SPSS 26 for Windows. The findings reveal that both organizational climate and job satisfaction are positively and significantly correlated with teacher commitment. These results highlight the importance of cultivating a supportive organizational climate and enhancing job satisfaction as strategies to reinforce teachers’ commitment to their schools. Keywords: Teacher, Teacher Commitment, Organizational Climate, Job Satisfaction Abstrak Komitmen guru berperan penting dalam keberhasilan pendidikan, namun masih banyak guru yang menunjukkan rendahnya komitmen, seperti minimnya keterlibatan dalam membimbing siswa, kurangnya kesiapan guru dalam merancang dan melaksanakan pembelajaran, kurangnya kepatuhan terhadap aturan sekolah dan guru yang justru mencari peluang kerja lain di luar profesi guru. Komitmen ini diduga dipengaruhi oleh berbagai faktor, di antaranya iklim organisasi dan kepuasan kerja. Adapun tujuan penelitian ini adalah untuk menguji apakah termuat hubungan antara iklim organisasi dan kepuasan kerja dengan komitmen guru. Metode yang digunakan adalah kuantitatif korelasional dengan teknik total sampling terhadap 125 guru SMA di Kecamatan Menganti, Gresik. Analisis data dilakukan dengan uji Spearman Rho dengan bantuan SPSS 26 for windows. Hasil menunjukkan bahwa baik iklim organisasi dan kepuasan kerja memiliki hubungan positif dan signifikan dengan komitmen guru. Temuan ini menegaskan pentingnya membangun iklim kerja yang positif dan meningkatkan kepuasan kerja guna memperkuat komitmen guru terhadap sekolah. Kata kunci: Guru, Komitmen Guru, Iklim Organisasi, Kepuasan Kerja